Pemberdayaan Masyarakat dengan Budidaya Vanili Berbasis Pupuk Organik di Kelurahan Rancamaya - Wiwit Irawati; I Ketut Wenten; Alexander Raphael (Abdimisi, 2022)
AbstractVanilla is a productive plant with yields that are quite high in economic value and the cultivation process can be carried out on land that is not too large. This Community Service is in collaboration with Rancamaya Village, Bogor Municipality, West Java Province, Indonesia. In this activity, the lecturer team worked closely with the Rancamaya Bogor Village Head. The objectives of this PKM are (1) empowering and increasing the knowledge of farmer group members about how to cultivate vanilla in a semi-modern way, (2) empowering vanilla farmer groups through increasing knowledge in increasing vanilla fruit production and (3) empowering the community to increase knowledge of the entrepreneurial spirit. PKM is carried out by giving a presentation delivered by a resource lecturer and followed by a question-and-answer session. It is hoped that with this guide to the community, the people of Rancamaya Village, Bogor can (1) understand that empty land or available land can be used to increase residents' income by cultivating vanilla, (2) the community is more aware that vanilla cultivation can be an alternative business to increase the people's economy, and (3) the community is more aware that vanilla plants have a sale value that can improve the people's economy